The Gothic and death - Davison, Carol Margaret (Manchester : Manchester University Press, 2017)
"The Gothic and death offers the first ever published study devoted to the subject of the Gothic and death across the centuries. It investigates how the multifarious strands of the Gothic and the concepts of death, dying, mourning and memorialisation ('the Death Question') - have intersected and been configured cross-culturally to diverse ends from the mid-eighteenth century to the present day. Drawing on recent scholarship in such fields as Gothic Studies, film theory, Women's and Gender Studies and Thanatology Studies, this interdisciplinary collection of fifteen essays by international scholars combines an attention to socio-historical and cultural contexts with a rigorous close reading of works, both classic and lesser known. This area of enquiry is considered by way of such popular and uncanny figures as corpses, ghosts, zombies and vampires, and across various cultural and literary forms such as Graveyard Poetry, Romantic poetry, Victorian literature, nineteenth-century Italian and Russian literature, Anglo-American film and television, contemporary Young Adult fiction and Bollywood film noir."--Publisher.
pt. I. Gothic graveyards and afterlives -- 1. Past, present, and future in the Gothic graveyard / Serena Trowbridge -- 2. 'On the very Verge of legitimate Invention': Charles Bonnet and William Blake's illustrations to Robert Blair's The Grave (1808) / Sibylle Erle -- 3. Entranced by death: Horace Smith's Mesmerism / Bruce Wyse -- pt. II. Gothic revolutions and undead histories -- 4. 'This dreadful machine': the spectacle of death and the aesthetics of crowd control / Emma Galbally and Conrad Brunström -- 5. Undying histories: Washington Irving's Gothic afterlives / Yael Maurer -- 6. Deadly interrogations: cycles of death and transcendence in Byron's Gothic / Adam White -- pt. III. Gothic apocalypses: dead selves/dead civilizations -- 7. The annihilation of self and species: the ecoGothic sensibilities of Mary Shelley and Nathaniel Hawthorne / Jennifer Schell -- 8. Death cults in Gothic 'Lost World' fiction / John Cameron Hartley -- 9. Dead again: zombies and the spectre of cultural decline / Matthew Pangborn -- pt. IV. Global Gothic dead -- 10. A double dose of death in Iginio Ugo Tarchetti's 'I fatali' / Christina Petraglia -- 11. Through the opaque veil: the Gothic and death in Russian realism / Katherine Bowers -- 12. Afterdeath and the Bollywood Gothic noir / Vijay Mishra -- pt. V. Twenty-first-century Gothic and death -- 13. Dead and ghostly children in contemporary literature for young people / Michelle J. Smith -- 14. Modernity's fatal addictions: technological necromancy and E. Elias Merhige's Shadow of the Vampire / Carol Margaret Davison -- 15. 'I'm not in that thing you know ... I'm remote. I'm in the cloud': networked spectrality in Charlie Brooker's 'Be Right Back' / Neal Kirk.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Gothic fiction (Literary genre), English -- History and criticism; Death in literature; Death in motion pictures; Mort dans la littérature.; Mort au cinéma.; LITERARY CRITICISM / Gothic & Romance; Death in literature; Death in motion pictures; Gothic fiction (Literary genre), English; Criticism, interpretation, etc